2023
DOI: 10.1039/d3cc03425a
|View full text |Cite
|
Sign up to set email alerts
|

The compression of deformed microgels at an air/water interface

Takahisa Kawamoto,
Kohei Yanagi,
Yuichiro Nishizawa
et al.

Abstract: The compression of microgels at air/water interfaces was investigated using a Langmuir–Blodgett trough with in situ fluorescent microscopy. The relationship between the structure of the microgel arrays and the compression behavior was clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 72 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…16 In this framework, mechanical and visco-elastic properties of air–water and oil–water microgel-covered interfaces have been investigated by means of interfacial rheology and surface pressure measurements to determine how microgel conformation, packing and film stability change in response to compression. 17–22…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 In this framework, mechanical and visco-elastic properties of air–water and oil–water microgel-covered interfaces have been investigated by means of interfacial rheology and surface pressure measurements to determine how microgel conformation, packing and film stability change in response to compression. 17–22…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the transfer of a microgel monolayer from a fluid interface to a solid substrate might introduce artifacts, raising concerns about the reliability of observed solid-to-solid isostructural phase transitions. 21,44…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent ex situ experimental observations have reported that microgels crystallize in hexagonal lattices and undergo a solid-to-solid transition with increasing concentration [25,26]. The structure of the monolayer has also been addressed in situ [27,28], where important differences have been observed with respect to ex situ measurements. It thus appears fundamental to address the properties of the monolayer by in situ techniques [29,30] and by appropriate theoretical modeling [22,31,32].…”
mentioning
confidence: 99%